Bioremediasi sebagai Alternatif Pengembalian Fungsi Tanah yang Tercemar Minyak Bumi - Zana Zafira (Jurnal Jaring SainTek, 2021)
Oil contamination from field drilling waste is a serious environmental problem worldwide. These oil contaminants must be removed to maintain biodiversity and ecological balance. Bioremediation is a soil cleaning technique that utilizes the metabolic ability of microorganisms to degrade soil contaminants. The use of native bacteria producing biosurfactants and utilization of hydrocarbons increases the effectiveness of bioremediation by making hydrocarbons bioavailable for degradation. Determination of bioremediation microorganisms affects the degradation process of petroleum. This is because each microorganism requires a specific substrate to reduce all the components of petroleum in the soil. A deeper approach is needed to obtain the effectiveness of microorganisms, both nonindigenous and indigenous microorganisms that are applied by researchers in degrading petroleum. However, not all available journal summaries provide a detailed explanation of the method and effectiveness of microorganisms in the bioremediation method. In this review, we will provide several microorganisms and methods used in bioremediation, including adsorptive bioremediation, biopile, in-situ bioremediation, landfarming, biostimulation, and composting in order to find the most effective method in the petroleum bioremediation process.